(untitled) (Ameghiniana, 2013)
A revision of the described trace fossils on rock from the Lower Palaeozoic in Argentina. A synthetic conspectus on the main concepts ernployed in the trace fossils study, including their morphology, ethology, taxonorny, etc. is provided. It follows a cription of the different ichnogenera known from Argentina, according to chronological and palaeoenvironmental criteria. They are arranged in the following groups: a) Lower Cambrian in the Nereites facies; b) Upper Cambrian in the Skolithos facies; c) Ordovician and Silurian in the Skolithos and Cruziana facies; d) Silurian and Devonian in the Zoophycos and Nereites facies. Each of them is figured and localized by the aid of palaeogeographic diagrams.